The Effect of Leadership, Self-Efficacy and Work Motivation on Work Discipline With Organizational Commitment as an Intervening Variable: Pengaruh Kepemimpinan, Efikasi Diri Dan Motivasi Kerja Terhadap Disiplin Kerja Dengan Komitmen Organisasi Sebagai Variabel Intervening - Fisabilillah Ibnu Roy; Sumartik Sumartik (Academia Open, 2021)
Organization is a form of cooperation of a group of people to achieve a certain goal effectively and efficiently. This study aims to determine the effect of leadership, self-efficacy and motivation on work discipline with organizational commitment as an intervening variable conducted at the Department of Environment and Hygiene, Sidoarjo Regency. This research uses quantitative research. The location of this research was conducted at the Department of Environment and Hygiene, Sidoarjo Regency. The population in this study were all permanent employees of the Environmental and Hygiene Service of Sidoarjo Regency. The sample is 97 employees. With total sampling technique. Collecting data using a questionnaire. Data analysis uses Path analysis with the help of PLS ​​SEM software data processing. The results of the study prove that leadership, self-efficacy and motivation have an effect on organizational commitment and work discipline. Leadership Self-efficacy and motivation affect work discipline through organizational commitment as an intervening variable